Designing Drone Game for Construction Site Inspection - Lawani, Kenneth; Hare, Billy; Cameron, Iain; Homatash, Hamid; Campbell, Julie (Frontiers in Built Environment, 2022)
The use of drone technology in the construction sector promises faster and more streamlined working practices. Forward-thinking contractors are investing in digitizing their operations and the use of drones with the capability of providing real-time site information is already a reality. Deploying drones for site inspections can help construction and safety managers avoid placing workers in precarious situations and the ability to quickly gather site aerial data can be invaluable. This study focuses on creating a drone flying game for inspecting construction sites and identifying potential safety hazards. The single-player, user-focused game comprises of fun flying mechanics to control the drone and this is an integral part of enabling users to gain the experience of simulated flying of a real drone. The game platform is the WebGL for rendering interactive 3D graphics within any compatible web browser without the use of plug-ins. The target audience for user experience and usability testing are construction and safety managers, construction professionals and students working in the industry. Preliminary findings with 47 participants revealed that the drone game was fun to play; the game was intuitive and easy to pilot the drone; the hazards in the simulated construction environment looked real; and the game satisfies the main aim of the playtest. The skills acquired from playing the educational drone game for site inspection and monitoring can successfully be applied when flying a real drone on a construction site. The significance of learning how to fly drones for site inspection during Covid-19 pandemic where workers need to be physically distanced is timely and relevant.